2008
DOI: 10.1016/j.actamat.2008.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Origin of intragranular crystallographic misorientations in hot-dip Al–Zn–Si coatings

Abstract: The origin of intragranular variations of the crystallographic orientation in hot-dip Al-Zn-Si coatings is discussed based on new experimental results and modelling. The solidification microstructure in as-received 55Al-43.4Zn-1.6Si (in wt.%) coatings deposited on steel plates in an industrial production line was analyzed by electron backscattered diffraction, glow-discharge optical emission spectroscopy and atomic force microscopy (AFM). The results were compared with those obtained in coatings re-solidified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Microalloying elements in aluminum-zinc based alloys alter properties by changing the morphology, chemistry, structure, spatial distribution and size of precipitates. It was found that Mg, Si and RE (rare-earth) as alloying elements can significantly improve characteristics of the Al-Zn based alloy, such as AZ alloy [1][2][3] and alloy coating [2,4]. The solid solution phases (Al) and (Si) and the intermetallics Mg 2 Si and MgZn 2 are able to improve the wear resistance of Al-Zn based alloy and the corrosion resistance of the hot-dip Al-Zn alloy coating.…”
Section: Introductionmentioning
confidence: 97%
“…Microalloying elements in aluminum-zinc based alloys alter properties by changing the morphology, chemistry, structure, spatial distribution and size of precipitates. It was found that Mg, Si and RE (rare-earth) as alloying elements can significantly improve characteristics of the Al-Zn based alloy, such as AZ alloy [1][2][3] and alloy coating [2,4]. The solid solution phases (Al) and (Si) and the intermetallics Mg 2 Si and MgZn 2 are able to improve the wear resistance of Al-Zn based alloy and the corrosion resistance of the hot-dip Al-Zn alloy coating.…”
Section: Introductionmentioning
confidence: 97%
“…It can be concluded that the content of the aluminum gradually decreases from the depth of 30 µm to the substrate, which is benefit to the improvement of the interfacial bonding strength. Results suggest that the maxima of Al is observed in the vicinity of the two boundaries due to the preferred areas for the growth of the primary Al dendrites after solidification starts . X‐ray diffraction pattern in Fig.…”
Section: Resultsmentioning
confidence: 90%
“…The misorientation value from the centre of the dendrites to the grain boundary is usually in the range of 1 to 2 degrees, sometimes even 5 degrees. The misorientation phenomenon is known in the literature and is explained by the thermal stresses induced by differential thermal expansion of the coatings and the steel substrate or micro-segregation during solidification of the coating 5 , 6 .
Figure 6 Top-view EBSD mapping IPF in Z direction; ( a ) as-received and ( b ) and ( c ) laser-remelted.
…”
Section: Resultsmentioning
confidence: 99%
“…The solidification process of the coating overlay is initiated by the formation of aluminium nuclei on the intermetallic layer and the growth of the primary phase through the coating thickness and then laterally in two dimensions, parallel to the steel sheet 5 . It has been shown that there is no texture correlation between the substrate and the coating overlay, and the crystallographic misorientation within a single grain is relatively high, especially in the large grains 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%